2019
DOI: 10.1111/inm.12619
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable factors affecting inpatient violence in an acute child and adolescent psychiatric unit: A 16‐year retrospective study

Abstract: Violent incidents in acute inpatient units for children and adolescents are a major and persistent problem. The demographic, clinical, and modifiable (environmental–organizational) risk factors that affect inpatient violence in an Acute Child and Adolescent Psychiatric Unit were investigated via a retrospective study. Data were collected from nursing and medical reports and the unit's census and included 100 days per year for 16 years. Incidents of violence and assault types were recorded, and variables such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…There has also been an increase in the use of antipsychotics [ 71 ], which may help to decrease violence, because they are often used to tackle aggressive behavior [ 72 ]. On the other hand, the high demand for inpatient treatment increases the risk of overcrowded CAP wards, which increases the risk for violence [ 28 , 73 ]. An interesting finding was that the decreases in violence were associated with shorter LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been an increase in the use of antipsychotics [ 71 ], which may help to decrease violence, because they are often used to tackle aggressive behavior [ 72 ]. On the other hand, the high demand for inpatient treatment increases the risk of overcrowded CAP wards, which increases the risk for violence [ 28 , 73 ]. An interesting finding was that the decreases in violence were associated with shorter LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient admission is often triggered by an acute psychiatric crisis, with a need to stabilize symptoms. These may include suicidality, violent behavior and significant impairment in daily functioning [26][27][28][29][30]. Only a minority of children and adolescents with mental healthcare needs are treated in hospitals, but inpatient treatment accounts for a significant share of the resources allocated to CAP [21,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies found a reduction in aggressive incidents and seclusions following improvements in the ward design or interior (Jenkins, Dye, & Foy, 2015;Ulrich, Bogren, Gardiner, & Lundin, 2018;van der Schaaf, Dusseldorp, Keuning, Janssen, & Noorthoorn, 2013). Other ward features associated with aggression include: poor staffing levels, boredom, lack of privacy and freedom, vague ward policies and ward turmoil (Duxbury, Bjorkdahl, & Johnson, 2006;Panagiotou, Mafreda, Moustikiadis, & Prezerakos, 2019).…”
Section: Ward Featuresmentioning
confidence: 99%